Spatial analysis of environmental health risks: A case of Bahawalpur district, Pakistan - Asad Ali Khan; Munazza Fatima; Kinza Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Environmental degradation is causing serious health threats to the population worldwide. This condition is becoming worse in the developing countries. Keeping in view various environmental health problems of Pakistan, the main objective of this research article is to analyze the spatial distribution of environmental risk factors in Bahawalpur district. Data has been mainly taken from the last report of Multiple Indicator Cluster Survey (2007-2008) of Bahawalpur district, compiled by the Punjab Bureau of Statistics. First, the study exposes the geographical and demographical setting of the district including all its sub administrative units, Ahmadpur East, Khairpur Tamewali, Yazman, Hasilpur Bahawalpur Sadder, and Bahawalpur City. Second, a number of environmental health indicators have been focused. These include, use of improved water sources, household water treatment, physical access to source of water, sanitation, bacterial concentration in water, disposal of excreta, disposal of waste water, disposal of solid waste and hand washing habits. Results reveal that existing state of these indicators offer a sort of environment that is prone to a number of serious health risks. For planners and policy makers, the study suggests a set of strategies and policies to address the local environmental issues and to minimize the health risks through administrative environmental management and community participation.
Keywords: 330; Environment; Health Threats; Water Quality; Air Pollution; Sanitation and Community Participation